A Macro-Model Approach to Monetary Policy Analysis and Forecasting for Vietnam - Dizioli, Allan (IMF Working Papers; Working Paper ;, 2015)
The paper develops a small New-Keynesian FPAS model for Vietnam. The model closely matches actual data from 2000-2014. We derive an optimal monetary policy rule that minimizes variability of output, inflation, and the exchange rate. Compared to the baseline model, the optimal rule places a larger weight on output stabilization as the intermediate target to achieve inflation stability, while allowing greater exchange rate flexibility. We analyze the dynamics of key macro variables under various shocks including external and domestic demand shocks and a lift-off of U.S. interest rates. We find that the optimal monetary policy rule delivers greater macroeconomic stability for Vietnam under the shock scenarios.